Spatial Distributions of Tourist in Langkawi Island - Norizawati, Mohd Ayob; Azizul, Ahmad; Badaruddin, Mohamed (2013)
Langkawi Island is most competitive tourist destination in Malaysia. Tourism industry in Langkawi boost in late 1980's after this destination declared as free-duty Island. From 2005 until 2011, tourism industry in Langkawi Island always recorded the positive growth and the next development will continues in more intensive phase after Langkawi Tourism Blueprint launched in 8 December 2011. With mission the transform Langkawi as one among top 10 global islands and ecoadventure destination in 2015, the process of development in Langkawi will more focusing on product development, infrastructures and enablers. Langkawi Island formed by 104 different and because of that, this destination can offer many type of attractions started from its scenic beauty to natural heritage until to the legends story. The understanding of tourist distribution can provided the good information especially for tourism market segmentations in Langkawi. With the understanding, the location and allocation of tourism services and facilities can be optimized and it also can use as a basic of forecasting future tourist behavior. Generally, the knowledge about whereabouts of tourists assists in tourism development and planning. Using Spatial Analyst tools in Geographic Information Systems (GIS) ArcGIS 10 software, this paper tries to identify the most visited attractions by 500 tourists in Langkawi Island on 2011. From the 500 respondent, 35 attractions in Langkawi Island were visited.